Energy transfer between rare earths in layered rare-earth hydroxides. Issue 7 (17th January 2018) - Feng, Pingping; Wang, Xinying; Zhao, Yushuang; Fang, De-Cai; Yang, Xiaojing
Abstract : In LRHs, the energy transfer between rare earths in adjacent layers was more efficient than that between neighboring rare earths in intralayers. Abstract : Energy transfer between rare earths in layered rare-earth hydroxides (LRHs) is worth the intensive study because the hydroxyls that act as the bridge connecting the neighbouring rare earths would generate non-radiative transitions. This study focuses on the energy transfer in the intralayer and the adjacent layers of LRHs. A series of LEu x Tb1− x Hs ( x = 0, 0.05, 0.2, 0.5, 0.8, and 0.95) was synthesized, the basal spacing ( d basal ) was adjusted from 8.3 to 46 Å through ion-exchange process, and unilamellar nanosheets were prepared through a delamination process. The luminescence behaviours of the samples demonstrated the following: (1) for the delaminated nanosheets, the quenching effect of both Eu 3+ and Tb 3+ was hardly observed. This implies that in the intralayer, the efficiency of energy transfer is extremely low, so that highly-concentrated co-doping does not influence the luminescence and by controlling the Eu/Tb molar ratio, white light can be obtained. (2) For small d basal, e.g., 27 Å, the fluorescence quenching of Tb 3+ and Eu 3+ was remarkable, while for large d basal, e.g., 46 Å, the emission of Tb 3+ emerged and the self-quenching between Eu 3+ ions weakened. (3) The energy transfer efficiency deceased with an increase in the distance between adjacent layers. In other words, either the energy transfer between Eu 3+ and Tb 3+ or the energy migration between Eu 3+ ions was more efficient when they were located in adjacent layers than in intralayers even when they were the nearest neighbours.